Suicide prevention for the veterinary profession—a preliminary investigation to explore veterinarians’ perceptions of ASIST training for their profession - Smith, Judith; Hawgood, Jacinta (Frontiers in Veterinary Science, 2025)
Background and aimsSeveral studies have identified that veterinarians are at higher risk of suicide than the general population. To date there has been scant attention to preventing suicide within this profession. Applied Suicide Intervention Skills Training (ASIST) is an evidence-based suicide prevention training program that aims to enhance trainees’ capabilities to help individuals who may be vulnerable to suicidality. ASIST has been successfully delivered to industries and professions where suicide is known to be a high risk and was therefore proposed as a potentially suitable suicide prevention initiative for translation to the veterinary profession. The aim of this study was to conduct a preliminary qualitative evaluation of the ASIST workshop delivered to veterinarians in Queensland, Australia. A secondary aim was to explore veterinarians’ perceived needs for suicide prevention in their profession.MethodAn Interpretative Phenomenological Analysis (IPA) framework was used to explore the experiences of a sample of Queensland veterinarians, after attendance at an ASIST workshop. Participants were females (87.5%) and males (12.5%) aged 30 to 66 years (M = 45, SD = 12.37) who engaged in individual interviews. Thematic analysis identified common and important patterns of meaning within the data.ResultsThree main themes and associated sub-themes were identified: Impactful workshop delivery and learning environment; Relevance of ASIST training for the veterinary profession; and Unique challenges and needs for suicide prevention in the veterinary profession. Overall, participants reported positive experiences of the workshop and its delivery. However, participants also reported feeling a level of discomfort related to some aspects of their participation and made suggestions for tailoring of the workshop to better fit the needs of their peers in future workshop delivery. Participants also suggested important targets for suicide prevention in the veterinary profession.ConclusionThis study identified key experiences of veterinarians who participated in the ASIST workshop. Important directions for future delivery of the ASIST workshop to the veterinary profession as well as directions for suicide prevention were suggested including actions for improving mental health and well-being in the workplace.